1988
DOI: 10.1099/00222615-27-1-71
|View full text |Cite
|
Sign up to set email alerts
|

The role of diarrhoeagenic Escherichia coli in acute diarrhoeal diseases in Bandar-Abbas, Iran

Abstract: Summary.The prevalence of different types of diarrhoea-producing Escherichia coli was measured in 273 patients attending 12 out-patient clinics in Bandar-Abbas, State of Hormozgan, Iran, during March 1984. Enteropathogenic E. coli (EPEC) belonging to 12 different serogroups, of which 0128 and 0126 were the most common, were found in almost 31% of the patients. Enterotoxigenic strains of E. coli (ETEC) were the next most frequent group (21.9%); among these, 36 (60%) strains produced heatstable enterotoxin (ST),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…Regardless of the difference in bacterial pattern of acute diarrhea, this difference can be due to technical problems in sampling and isolation of Campylobacter strains. 18,28 Yersinia was not found in this study however, its rate in children with diarrhea was 2.7% in another report. 29 Diarrheagenic E. coli is among the most prevalent causative agents in acute diarrhea in Iran, particularly in children.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Regardless of the difference in bacterial pattern of acute diarrhea, this difference can be due to technical problems in sampling and isolation of Campylobacter strains. 18,28 Yersinia was not found in this study however, its rate in children with diarrhea was 2.7% in another report. 29 Diarrheagenic E. coli is among the most prevalent causative agents in acute diarrhea in Iran, particularly in children.…”
Section: Discussioncontrasting
confidence: 59%
“…4,11e16 Shigella is an important pathogen in developing countries and one of the most important etiological agents of acute diarrhea in Iran, especially in children. 17,18 In this study Shigella spp. was isolated in 148 (13.5%) of all patients, similar to another study conducted in Iran 17 but sensibly higher than previous studies in Iran 10,19e21 as well as many other developing countries.…”
Section: Discussionmentioning
confidence: 76%
“…The referenced studies indicated a higher frequency of ST-ETEC in Latin America/ the Caribbean, the Middle East/North Africa, and South Asia. In Iran, Katouli et al showed that ST was the most frequent toxin type (60z) followed by LT/ST and LT (20). Samples collected in 1998 showed a prevalence of the LT type (36).…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al highlighted a need for more information on the distribution of ETEC phenotypes (18). The role of ETEC in diarrhea1 disease in Iran has not been widely studied (19)(20)(21). Hence, the present study was designed to characterize the phenotypes and genotypes of ETEC associated with diarrhea among Iranian children aged less than 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Similarities between the strains were calculated as correlation coefficients as described before [21] and clustered according to the unweighted pair group method with arithmetic averages (UPGMA) [22] yielding a dendrogram. An identity level of 0.975 was set based on reproducibility of the system as described before [23]. Strains showing similarities to each other higher than this value were regarded as identical and assigned to the same PhP types and those not identical to any other isolates were called single (Si) PhP types.…”
Section: Ansaruzzaman Et Almentioning
confidence: 99%